Advances in tethered photopharmacology for precise optical control of signaling proteins. (April 2022) - Broichhagen, Johannes; Levitz, Joshua
Abstract: To overcome the limitations of traditional pharmacology, the field of photopharmacology has developed around the central concept of using light to endow drug action with spatiotemporal precision. Tethered photopharmacology, where a photoswitchable ligand is covalently attached to a target protein, offers a particularly high degree of spatiotemporal control, as well as the ability to genetically target drug action and limit effects to specific protein subtypes. In this review, we describe the core engineering concepts of tethered pharmacology and highlight recent advances in harnessing the power of tethered photopharmacology for an expanded palette of targets and conjugation modes using new, complementary strategies. We also discuss the various applications, including mechanistic studies from the molecular biophysical realm to in vivo studies in behaving animals, that demonstrate the power of tethered pharmacology. Highlights: Photopharmacology uses light-responsive drugs to optically control signaling proteins. Chemical tethering of such drugs allows maximal spatiotemporal and genetic precision. Recent design strategies drive increasing efficiency and target specificity. Tethered photopharmacology enables applications from molecular biophysics to behavior.